Accidents with sharp objects involving biological material: what Dentistry undergraduate students say and what they do - Mazutti, William José (2018)
Considering the importance of adopting biosafety measures since the initial training of dental surgeons, this study aimed to describe the prevalence, the distribution and to verify the attitudes of Dentistry students in relation to prevention and management of accidents with sharp cutting objects. This was a quantitative-qualitative observational study with 58 undergraduates from a Dentistry course in Rio Grande do Sul. Questionnaires and participant observations were used. We verified a 31% prevalence of accidents involving biological material. The most frequent sites were the periodontics clinic and the sterilization center. Periodontal probes, ultrasonic tips and endodontic files were the most involved instruments. We identified failures in the notification process and limitations in the proper use of PPE, especially in the sterilization lab. Aspects such as vaccination, hand washing and disinfection routines require follow-up. Disrespect for biosafety standards and the lack of attention were important risk factors observed. The findings demand investments in ongoing education to raise awareness of the academic community, which is indispensable for accidents’ prevention and preservation of the future dental surgeons’ health.